Diagnosis and treatment of late-onset Pompe disease in the Middle East and North Africa region: consensus recommendations from an expert group. Issue 1 (December 2015) - Al Jasmi, Fatma; Al Jumah, Mohammed; Alqarni, Fatimah; Al-Sanna'a, Nouriya; Al-Sharif, Fawziah; Bohlega, Saeed; Cupler, Edward; Fathalla, Waseem; Hamdan, Mohamed; Makhseed, Nawal; Nafissi, Shahriar; Nilipour, Yalda; et al.
Abstract Background Pompe disease is a rare autosomal recessive disorder caused by a deficiency of the lysosomal enzyme alpha-glucosidase responsible for degrading glycogen. Late-onset Pompe disease has a complex multisystem phenotype characterized by a range of symptoms. Methods An expert panel from the Middle East and North Africa (MENA) region met to create consensus-based guidelines for the diagnosis and treatment of late-onset Pompe disease for the MENA region, where the relative prevalence of Pompe disease is thought to be high but there is a lack of awareness and diagnostic facilities. Results These guidelines set out practical recommendations and include algorithms for the diagnosis and treatment of late-onset Pompe disease. They detail the ideal diagnostic workup, indicate the patients in whom enzyme replacement therapy should be initiated, and provide guidance on appropriate patient monitoring. Conclusions These guidelines will serve to increase awareness of the condition, optimize patient diagnosis and treatment, reduce disease burden, and improve patient outcomes.